Psychological Well-Being in Adolescents with Different Types of Socialization - Elena N. Volkova (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. Psychological well-being is a criterion for assessing the type of adolescent's socialization processes. According to EPOCH model, the psychological well-being includes the adolescent's engagement, perseverance, optimism, connectedness, happiness. The correlation of psychological well-being and prosocial behaviour forms four types of socialization processes: positive, deviant, traumatic and negative socialization.